1986
DOI: 10.1037/0735-7028.17.4.313
|View full text |Cite
|
Sign up to set email alerts
|

The failure of clinical psychology graduate students to apply understood ethical principles.

Abstract: and a member of the Tennessee Bar. His research interests include professional issues and the general interface between psychology and the law. Clinical interests focus on marriage counseling and group psychotherapy. CARMEN S. JARA received her master's degree in psychology at Memphis State University in 1984 and is currently living in San Francisco, California.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 8 publications
5
50
0
1
Order By: Relevance
“…No association was found between preparedness to address unethical conduct by a colleague and degree level or years of work experience. Previous studies reported that graduate students and practitioners have difficulty confronting unethical conduct by their peers (e.g., Bernard & Jara, 1986; Betan & Staton, 1999; Tryon, 2000). Multilevel university training in ethics, however, appears to help practitioners feel better prepared to tackle this difficult task, perhaps by providing more opportunities to discuss or role‐play how to handle such a scenario (see Koocher & Keith‐Spiegel, 2008, pp.…”
Section: Discussionmentioning
confidence: 99%
“…No association was found between preparedness to address unethical conduct by a colleague and degree level or years of work experience. Previous studies reported that graduate students and practitioners have difficulty confronting unethical conduct by their peers (e.g., Bernard & Jara, 1986; Betan & Staton, 1999; Tryon, 2000). Multilevel university training in ethics, however, appears to help practitioners feel better prepared to tackle this difficult task, perhaps by providing more opportunities to discuss or role‐play how to handle such a scenario (see Koocher & Keith‐Spiegel, 2008, pp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bernard, Murphy, and Little (1987) revealed that significant numbers of profess~onal clinicians would do less than they knew they should in dealing with unethical practices by colleagues. Bernard and Jara (1986) found that graduate students in clinical psychology were reluctant to report grossly unethical behavior. Tabachnik et al (1991) also found that some faculty are uncertain about the propriety of confronting a colleague on an ethical issue.…”
Section: Ethical Review Committeementioning
confidence: 97%
“…This latter issue has been discussed in the literature. Most violations go unreported (Welfel, 2006), and counselors generally are reluctant to confront or report the unethical behaviors of their peers (Bernard & Jara, 1986;Lowman, 2006). These findings are worrisome not only because of the continuing harm that may be caused to clients but also because public trust is based on a belief that counselors hold their fellow professionals to acceptable standards of ethical behavior (Herlihy & Corey, 2006;Remley & Herlihy, 2010).…”
Section: Ensuring Ethical Practicementioning
confidence: 99%